Theurgy: Rituals of Unification in the Neoplatonism of Iamblichus - Shaw, Gregory (Traditio, 1985)
In the late third century of the Common Era, the Platonic tradition was changed profoundly under the direction of Iamblichus of Chalcis, head of the Platonic school in Syria. Through the introduction of Egyptian and Chaldaean religious rites as part of the intellectual disciplines of his school, Iamblichus was given the honorific title ‘divine’ (θεĩος) by his Neoplatonic successors. Modern scholars, however, have generally not seen the head of the Platonic school's turning to magic rites as the high point of intellectual progress, and Iamblichus' contribution to Platonism has either been dismissed as a corruption of the tradition or has been left as an irresoluble enigma.